2020
DOI: 10.1002/2050-7038.12457
|View full text |Cite
|
Sign up to set email alerts
|

Impact assessment of aco‐optimizeddynamic line rating and transmission switching topology on network expansion planning

Abstract: Power system planning needs regular investment in transmission area to cope with the increasing load, network congestion, and large-scale integration of renewable generation. With the growth of renewable energy resources integration, electric utilities are faced with an increasingly complex operating environment. Utilities are in need of a series of cost-effective technologies which allow them to operate power systems more economically and reliably. Optimal transmission switching (OTS) and dynamic line rating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…Previous research has shown that using DTR, the transmission capacity can be increased from 15-50% and in some cases it could be up to 150% of the STR ratings [94]. In literature, DTR is utilized to increase transmission line capacity , which leads to improved RES integration [95], relieve network congestion [96], enhance system reliability [90], and can help postpone the need for building new transmission infrastructure [62]. The cost of DTR deployment is comparatively less (approx.…”
Section: A Ots With Dynamic Thermal Ratingmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has shown that using DTR, the transmission capacity can be increased from 15-50% and in some cases it could be up to 150% of the STR ratings [94]. In literature, DTR is utilized to increase transmission line capacity , which leads to improved RES integration [95], relieve network congestion [96], enhance system reliability [90], and can help postpone the need for building new transmission infrastructure [62]. The cost of DTR deployment is comparatively less (approx.…”
Section: A Ots With Dynamic Thermal Ratingmentioning
confidence: 99%
“…The main objective in including these short-term problems in the long-term problem network expansion is to exploit the operational flexibility of these two technologies, which could help in efficient utilization of the transmission infrastructure and could help in postpone/reduce additional investment in these assets. A co-optimized expansion planning model is proposed in [62] to add new generating units and transmission lines in the current network for the next 20 years. The model is used to decide the size, number, and location of the generating plants and lines for the said planning horizon.…”
Section: A Ots With Dynamic Thermal Ratingmentioning
confidence: 99%
See 1 more Smart Citation
“…The reliability of the joint operation of OTS and DLR is assessed in [48], where the authors showed that instead of degrading system reliability, the combined OTS and DLR topology can improve system reliability. Investment planning and transmission expansion problem using reconfigurable networks and DLR are studied in [49][39] [50]. C. RESEARCH GAP However, the current literature about the DLR enforcement with OTS in scheduling of power system network is based on deterministic modeling.…”
Section: B Related Workmentioning
confidence: 99%
“…Nowadays, the thermal rating assessment is a relevant problem for engineers and researchers dealing with power system operation and planning. Thermal ratings have a strong impact on the optimal solution of a power system scheduling [1], a wind power integration [2][3][4], a hosting capacity of substations [5], [6], an asset management [7] among many others [8]. Moreover, due climate change problem the system operators should manage a power system with a large share of Distributed Energy Resources (DER) [9].…”
Section: Introductionmentioning
confidence: 99%